1999
DOI: 10.1091/mbc.10.8.2595
|View full text |Cite
|
Sign up to set email alerts
|

The Nuclear Actin-related Protein ofSaccharomyces cerevisiae, Act3p/Arp4, Interacts with Core Histones

Abstract: Act3p/Arp4, an essential actin-related protein of Saccharomyces cerevisiae located within the nucleus, is, according to genetic data, involved in transcriptional regulation. In addition to the basal core structure of the actin family members, which is responsible for ATPase activity, Act3p possesses two insertions, insertions I and II, the latter of which is predicted to form a loop-like structure protruding from beyond the surface of the molecule. Because Act3p is a constituent of chromatin but itself does no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
91
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 119 publications
(94 citation statements)
references
References 41 publications
(60 reference statements)
1
91
0
Order By: Relevance
“…Yeast strains DY2864 (MATa his4-912δ-ADE2 his4-912δ lys2-128δ can1 trp1 ura3 ACT3), DY4285 (MATa his4-912δ -ADE2 lys2-128δ can1 leu2 trp1 ura3 act3-ts26) and DY4519 (MATa his4-912δ -ADE2 lys2-128δ can1 leu2 trp1 ura3 act3-ts12) were used for analyses of chromatin structure. To isolate new temperature-sensitive alleles of ACT3, a plasmid shuffle was performed as described (16,20). DNA sequencing shows that the act3-ts26 and act3-ts12 alleles each have a single amino acid substitution of G187R and G455S, respectively.…”
Section: Yeast Strains Media and General Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Yeast strains DY2864 (MATa his4-912δ-ADE2 his4-912δ lys2-128δ can1 trp1 ura3 ACT3), DY4285 (MATa his4-912δ -ADE2 lys2-128δ can1 leu2 trp1 ura3 act3-ts26) and DY4519 (MATa his4-912δ -ADE2 lys2-128δ can1 leu2 trp1 ura3 act3-ts12) were used for analyses of chromatin structure. To isolate new temperature-sensitive alleles of ACT3, a plasmid shuffle was performed as described (16,20). DNA sequencing shows that the act3-ts26 and act3-ts12 alleles each have a single amino acid substitution of G187R and G455S, respectively.…”
Section: Yeast Strains Media and General Methodsmentioning
confidence: 99%
“…Mononucleosomes were reconstructed in vitro with purified core histones of chicken (16) and a 180 bp DNA fragment recovered from BssHII-digested pBluescript SK+ (Stratagene) according to Tatchell and van Holde (21). Mobility shift assays were performed by mixing the reconstituted mononucleosome and the purified GST fusion protein in 10 µl of binding buffer (10 mM HEPES, pH 7.9, 50 mM KCl, 5 mM DTT, 5 mM PMSF, 4 mM MgCl 2 , 5% glycerol) for 15 min at 37°C and then by electrophoresis on 1.5% agarose gels in 1× TAE (8 mM Tris, 1 mM sodium acetate, 0.4 mM EDTA, pH 8.0).…”
Section: Mobility Shift Assay Of Mononucleosomesmentioning
confidence: 99%
See 2 more Smart Citations
“…In yeast, this actin/Arp4 module probably has also evolved into a less conserved Arp7/Arp9 dimer found in the SWI/SNF and RSC chromatin remodeling complexes [29]. It has been shown that Arp4 binds to all four histones in vitro and in vivo [30] and Arp8 binds to H3 and H4 with some preference in vitro [10], suggesting that the actin/Arp modules in chromatin modifying complexes might provide chaperone functions for the histone octamer and mediate the rearrangement of histone-histone, and/or histone-DNA contacts during chromatin remodeling. The defined actin-containing module in the INO80 complex provides a unique opportunity to understand the mechanism of nuclear actin.…”
Section: Introductionmentioning
confidence: 99%